2005
DOI: 10.1159/000085095
|View full text |Cite
|
Sign up to set email alerts
|

Differential Astrocyte Response to Theiler’s Murine Encephalomyelitis Virus Infection

Abstract: Objectives: We aimed to address if selective astrocyte apoptosis is involved in the lack of murine demyelinating disease following infection by the L*-1 variant of Theiler’s virus. In addition, we investigated whether L*-1-infected astrocytes were able to selectively express molecules whose effects would play a role as pathogenic factors. Methods: Murine cultured astrocytes were infected with two Theiler viruses, the DA strain and the mutated DA variant L*-1, which does not synthesize the out of frame L* prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Putative macrophages and activated astrocytes were found to be closely associated with areas of demyelination, a finding in agreement with previous research (Peña Rossi et al, 1997; Pozner et al, 2004; Rubio et al, 2006; Zheng et al, 2001). We also found that virus-positive cells were distributed centrally within newly forming lesions and in the periphery of more mature/developed lesions.…”
Section: 0 Discussionsupporting
confidence: 92%
“…Putative macrophages and activated astrocytes were found to be closely associated with areas of demyelination, a finding in agreement with previous research (Peña Rossi et al, 1997; Pozner et al, 2004; Rubio et al, 2006; Zheng et al, 2001). We also found that virus-positive cells were distributed centrally within newly forming lesions and in the periphery of more mature/developed lesions.…”
Section: 0 Discussionsupporting
confidence: 92%
“…[55][56][57][58] Also it has been reported for other microbial infections a cell-dependent susceptibility to apoptosis, 53,59 including a differential susceptibility of astrocytes and microglia. 60,61 TNF-␣ acts through two distinct cell surface receptors, TNFR1 and TNFR2. TNFR2 is expressed only on hematopoietic and endothelial cells, whereas TNFR1 is expressed on all cell types and initiates the majority of TNF-␣ biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation induces astrocytes to produce cytokines that increase the blood brain barrier permeability, allowing easier infiltration by leukocytes [119]. In response to IFN-γ, TNF-α, and TMEV infection astrocytes upregulate ICAM-1 and VCAM-1 adhesion molecules which aids in leukocyte recruitment [123-125]. In response to IL-17, astrocytes produce CCL2, CCL12, CXCL1, and CXCL2, a distinctly different profile compared to IFN-γ stimulation [13, 60].…”
Section: Astrocytesmentioning
confidence: 99%